Processor Performance - Shaikh, Abuzar; Nair, Gokul; Pathan, Arshad; Panda, Ashish; Shaikh, Shakila; Pappu, Shiburaj (International Journal of Computer Sciences and Engineering, 2019)
Since the computer is invented the main heart of the computer is the CPU (performance). We have researched from the earlier paper that processor was not enough to compute with the performance. This paper, explains the characteristics of processor performance and its implementation for several configurations, Including Intel quad core processor, Quad-core multi-processor, Quad Core CPU Chip having 4 cores on one single chip, Thread-Level Parallelism. Using the clock rate, the CPU’s execution time, which is the total time the processor takes to process some program in seconds per program (total number of bytes), can be calculated. We propose a performance evaluation methodology affected by a benchmark test. Measuring of such systems performance becomes an important task for any system embedded design process.